Make these toys : 101 clever creations using everyday items - Swain, Heather, 1969- (Perigee Book, 2010)
Provides instructions for making projects using inexpensive materials from around the house to craft a milk carton balloon boat, rubber band banjo, and an embroidery hoop tambourine.